Interaction between topic marking and subject preference strategy in sign language processing - Krebs, Julia; Malaia, Evie; Wilbur, Ronnie B.; Roehm, Dietmar (Language, cognition and neuroscience, 2020)
The preference of the human parser for interpreting syntactically ambiguous sentence-initial arguments as the subject of a clause (i.e. subject preference) has been documented for spoken and sign languages. Recent research (He, 2016) suggests that the subject preference can be eliminated by manipulating information structure (topicalisation). To investigate the effects of interaction between syntax and information structure on language processing, we tested the role of topic marking in sentence processing in Austrian Sign Language (ÖGS). We examined whether non-manual topic marking on the sentence-initial argument eliminates the subject preference using event-related brain potentials. We replicated the finding of the subject preference in ÖGS by identifying an N400-family response to object-first sentences. Further, topic marking in ÖGS influenced the processing of the topic argument itself and later processing stages. This suggests that interpretation of topic marking imposes additional processing costs, relative to syntactic reanalysis.